The Control Schemes Of Vehicle Steer By Wire System By Using Fuzzy Logic And Pid Controller - Mohd Tumari, Mohd Zaidi; Mohd Nasir, Muhamad Azidi; Saat, Shahrizal; A Subki, A Shamsul Rahimi; Abd Rashid, Wan Norhisyam; Suid, Mohd Helmi; Ghazali, Mohd Riduwan (Medwell Journals, 2018)
Recently, the Vehicle Steer-By-Wire (VSBW) system has improved significantly in terms of vehicle dynamics, comfort, safety, maneuverability and stability. VSBW eliminates the mechanical linkage between steering wheel and the front wheels which caused the practical problems for vehicle steering control. This study presents investigations into the development of PID and fuzzy logic control schemes for steering wheel returnability, directional control and wheel synchronization of a VSBW system. For PID control scheme, PD controller is used to control the returnability of steering wheel while PID controller is used to control the angle of front wheel. The Ziegler Nichols method is used for tuning the PID parameters. The fuzzy logic controller is used to control the returnability of steering wheel. The implementation environment is developed within LabView Software for comparison of performance for both control schemes. Implementation results of the response of the VSBW system with the PID and fuzzy logic controller are presented in time domains. The performances of control schemes are examined in terms of steering wheel returnability, directional control and wheel synchronization.